ANALISIS FUNGSI AKREDITASI SEKOLAH DALAM PENINGKATAN PRODUKTIVITAS SEKOLAH - Mhd Joni Marpaung; Zaini Dahlan Ihwan; El-Musthofa; Taufik Hidayat (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine and analyze the function of school accreditation in increasing school productivity. This research uses qualitative research with descriptive method. This research was conducted at is Islamic High School Al- Washliyah 49 Pasar Lembu. The subject of this research is the Principal/Vice Principal,. The data collection technique of this research is observation, interviews and documentation. The results of this study indicate that school/madrasah test scores in the last 3 (three) years can be extracted from the average test scores, the Islamic High School Al-Washliyah 49 Pasar Lembu has increased in the last three years as seen from the average test scores. This is due to the existence of tutoring apart from school, the school affiliates with several well-known tutors. Coupled with the free online tutoring. This is also supported by facilities and infrastructure, one of which is the school facilitating students with a kind of tablet to be able to access or look for things about lessons that have not been completed when studying in class. In addition, extracurricular activities at school also support students for their academic achievements. The existence of clubs such as science club, English club and many more. Then, judging from the public perception of the Madrasah Aliyah Al-Washliyah 49 Pasar Lembu, this school is very good, because this Islamic High School Al-Washliyah 49 Pasar Lembu has a fairly good Islamic base because of the holding of youth mosques. The academic achievements of the Islamic High School Al-Washliyah 49 Pasar Lembu it self have had many championships. One of them is in the district level madrasa science